The emergence of life : from chemical origins to synthetic biology - Luisi, P. L. (Cambridge University Press, 2006)
Uniquely combining biology and philosophy, this book offers a systematic course in the emergence of life from inanimate matter through to cellular life. With review questions included, this book will appeal to graduate students, academics and researchers in the field of the origin of life and other related areas.